Sensitivity of grain yield components to plant population density in non-prolific maize (Zea mays) hybrids - EMAM, Y (The Indian Journal of Agricultural Sciences, 2014)
A field experiment was conducted during 1995-96 to study the response of maize (Zea mays L,) hybrids to plant population density. Three non-prolific maize single cross hybrids (,SC 108, ’SC 301’ and ’SC 604’) were sown at 4 densities (5.56,6.67,8.33 aod 11.11 plants/m2) in (aodomized complete-block design, in split-plot with 4 replicates at Shiraz. The grain yield increased at higher population densities. This was owing to incrense in rate of grain-filling with no signifcant change in duration of grain-filling period. Kernelslear and kernels/ear row were the most important yield adjustment components in response to plant population density in all 3 hybrids. Weight/kernel, rows/ear and ears/plant had only a negligible effect in yield adjustment.